A study on job satisfaction among academic staff in Universiti Malaysia Perlis - Wong Sui Ying (School of Business Innovation and Technopreneurship, University Malaysia Perlis, 2012)
The purpose of this study was to examine the factors thst affecting job satisfaction among academic staff in University Malaysia Perlis (UniMAP). The objective of the study is to identify the demographic background and the factors that affecting job satisfaction among academic staff in UniMAP. Several factors had been identified , such as age, gender salary, working condition and personality that seem to be having significant effect on job satisfaction. The data was collected from a total of 70 respondents through questionaires distribution. Then, the data was analyzed by using Statistical Package for Social Science (SPSS) software. based on the data analysis, the result show that there were no significant relationships between job satisfaction and age, salary as well as working condition. It was only the factor of gender and personalities have significant impact on job satisfactions. The present study had provided a better understanding regarding the factors influencing job satisfactionamong academic staff in UniMAP.